Institutional framework of intellectual property development - Kukareka, Diana V. (Journal of the Belarusian State University. Economics, 2018)
The main goal of the article is to demonstrate alternative view on intellectual property institute and its influence on the innovations creation process. The article deals with the impact of intellectual property rights institution on motivation for research and development, as well as for creative activity and arts. The comparison and contraposition are established between fixing property rights on tangible resources and intangible or intellectual resources. The arguments are made on the point of no necessity in creating long term intellectual monopoly. The pros and cons of intellectual monopoly influence on scientific and economic progress were analysed. The reasons shown in the article open opportunities for the changes in economic policy aiming for institutional framework creation that provides free access to intellectual results for every citizen. It would help to stimulate intellectual activity of our own and to benefit from global technology and knowledge flow.